Progress in Endocrine Neoplasia - Wells, Samuel A. (Clin Cancer Res, 2016)
Most endocrine tumors are benign, and afflicted patients usually seek medical advice, because of symptoms caused by too much, or too little, native hormone secretion, or the impingement of their tumor on a vital structure. Malignant endocrine tumors represent a more serious problem, and patient cure often depends on early diagnosis and treatment. The recent development of novel molecular therapeutics, holds great promise for the treatment of patients with locally advanced or metastatic endocrine cancer. In this CCR Focus expert clinical investigators describe the molecular characteristics of various endocrine tumors, and discuss the current status of diagnosis and treatment.